Effect of Different Play-based Learning Approach and Anxiety towards Learning Free Style Swimming - Mandalawati, Titin Kuntum; Lisdiantoro, Ghon; Prasetyo, Yona Bayu; Bildhonny, Achmad Furqon (UNIB Press, 2025)
This study aims to determine: 1) the difference between play-based learning approaches using tools and peers in improving free style learning outcomes; 2) differences in free style learning outcomes among those with high, medium, and low levels of anxiety; 3) the significance from the interaction between play-based learning approach using tools and peers and level of anxiety towards learning results. This research uses an experiment method with 2 x 3 factorial design. Population of this study consists of 4th elementary school students in Barat District with 48 students as samples. Data is collected through tests and measuring. RCMAS (The Revised Children's Manifest Anxiety Scale) is used to measure anxiety. Results from the anxiety measurement are used to group/categorize: (1) samples with high anxiety; (2) moderate anxiety; and (3) low anxiety. Data is collected through measuring the distance reached by students in a post test. Then, data is analyzed by using 2-way ANOVA and Scheffe’s method with 5% significance. This research concluded that: 1) there is significant impact in the usage of tools and peers in improving free style learning outcome; 2) there is a notable difference in learning outcome among students with varying levels of anxiety; 3) there is no significance from the interaction between tool and peer-based learning and level of anxiety towards learning outcome.